PERAN MAHASISWA KKM 57 DESA PARIGI DALAM PENGUATAN LITERASI ANAK MELALUI PROGRAM MEMBACA NYARING - Umroh Umroh; Febrianti Satibi; Fikri Nur Alim; Gumelar Saktiana; Andriansah Andriansah; Frisky Friendly Jovial; Tb.Moch Riad All Fariz; Febryanna Rachmawati; Nova Eliza; Putri Sabrina; Shifa Hafizha Safira; Meidita Sabrina; Jihan De Sabilla; Syarif Abdullah (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Literacy skills serve as a fundamental pillar in supporting children's cognitive and socio-emotional development. Unfortunately, disparities in access to literacy resources remain prevalent, particularly in rural areas such as Parigi Village. The read-aloud program initiated by KKM 57 student volunteers emerged as a strategic effort to cultivate a joyful and inclusive reading habit among children in the community. This study adopts a descriptive qualitative approach to provide an in-depth account of the program's implementation and its impact on children's motivation and engagement in literacy activities. Data were collected through observations, interviews, and documentation during activities held at the